1995
DOI: 10.1159/000147763
|View full text |Cite
|
Sign up to set email alerts
|

Locational Relationship of the Supraorbital Notch or Foramen and Infraorbital and Mental Foramina in Koreans

Abstract: The morphology and locational relationship of the supraorbital notch/foramen, infraorbital foramen, and mental foramen were studied from photographs of 124 Korean skulls (male 35, female 18, unknown sex 71). The infraorbital foramen was on the sagittal plane passing through the supraorbital notch/foramen (36.4%), or lateral to the plane (63.6%). The mental foramen was either on the plane (69.3%), lateral to the plane (21.8%), or medial to the plane (9.0%). The supraorbital notch/foramen, infraorbital foramen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
73
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 3 publications
22
73
2
5
Order By: Relevance
“…Our study concluded that the MF is located at an average distance 15.2 mm and 12.6 mm from the IBM in dentate and edentulous mandibles, respectively. Considering the mean values for the distance MF-IBM in dentate mandibles, the results of the present study in Greeks were similar to that observed for Africans, Chinese and Thais [3,33] and higher than that related for British, Koreans and Americans [7,8]. The studies of Güler et al [13], Apinhasmit et al [3] and Amorim et al [2] reported a gender dimorphism, as the male mandibles of their sample presented higher values of MF-IBM distances than the female.…”
Section: Discussionsupporting
confidence: 87%
“…Our study concluded that the MF is located at an average distance 15.2 mm and 12.6 mm from the IBM in dentate and edentulous mandibles, respectively. Considering the mean values for the distance MF-IBM in dentate mandibles, the results of the present study in Greeks were similar to that observed for Africans, Chinese and Thais [3,33] and higher than that related for British, Koreans and Americans [7,8]. The studies of Güler et al [13], Apinhasmit et al [3] and Amorim et al [2] reported a gender dimorphism, as the male mandibles of their sample presented higher values of MF-IBM distances than the female.…”
Section: Discussionsupporting
confidence: 87%
“…Total 300 skulls were used for this study, the results were the mean distance between the infra orbital foramen and the infra orbital margin was 8 Vertical diameter 3.03+0.72mm…”
Section: Resultsmentioning
confidence: 99%
“…The study of the Infra orbital foramen is also basic to prevent the potential risk for iatrogenic injury during facial surgeries due to the presence of additional branches of the infra orbital nerve [19]. Previous studies show the relation between infra orbital foramen and the other anatomical structures, in studies with different purposes, what shows its importance as a repair point: distance between infra orbital foramen and an imaginary horizontal line in the piriform aperture base, inferior orbital fissure and the more inferior portion of the optical channel [21] medium facial line on an imaginary line that passes through the supraorbital incisure; eyes pupil and second premolars [22] medium sagittal plane and supraorbital incisures [23] and finally related to the piriform aperture [19]. The morphometric and morphological studies of foramens of skull and different bones of skull are more helpful in surgery practice and anthropometric studies [24,25].…”
Section: Measurement Of Iofmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies has been evaluated morphometric assessment of the IOF (Gruber, 1878;Gozdziewski et al, 1979;Bolini & Del Sol;Triandafilidi et al;Ochs & Buckley, 1993;Chapman et al,1995;Chung et al, 1995;Leo et al, 1995;Aziz et al;Karakas et al, 2002), nevertheless, the results presented large variance. This foramen has been used from various reference points, e.g.…”
Section: Introductionmentioning
confidence: 99%